Pigment-protein complexes of thylakoid membranes of Deschampsia antarctica Desv. Plants - Taran, N.Yu.; Ozheredova, I.P.; Storozhenko, V.О.; Svetlova, N.B.; Topchiy, N.М. (Український антарктичний журнал, 2010)
The molecular analysis results of pigment-protein complexes of photosynthetic membranes of Deschampsia antarctica plants, one of the native representatives of the Antarctic region are presented. Bioinformatics searching of genome products of Deschampsia antarctica in available protein databeses related to the structure and function of plastids was carried. The searching of Arabidopsis thaliana and Oryza sativa japonica homolog search submitted in free databases is also performed. The results of comparative analysis of primary sequences of the known and potential products are presented. Приведены результаты молекулярного анализа пигмент-белковых комплексов и рассмотрены особенности липидного состава фотосинтетических мембран Deschampsia antarctica – одного из представителей флоры Антарктики. Осуществлен биоинформационный поиск в доступных базах данных продуктов генома Deschampsia antarctica, которые структурно и функционально связаны с пластидами. Также осуществлен поиск их гомологов в протеомах Arabidopsis thaliana и Oryza sativa japonica. Приведены результаты сравнительного анализа первичных последовательностей потенциальных и известных продуктов. Наведено результати молекулярного аналізу пігмент-білкових комплексів і розглянуто особливості ліпідного складу фотосинтетичних мембран Deschampsia antarctica – одного з представників флори Антарктиди. Здійснено біоінформаційний пошук у доступних базах даних продуктів геному Deschampsia antarctica, які структурно та функціонально пов'язані з пластидами. Також здійснено пошук їх гомологів у протеомах Arabidopsis thaliana та Oryza sativa japonica. Наведено результати порівняльного аналізу первинних послідовностей потенційних та відомих продуктів.